Immune Toxicity with Checkpoint Inhibition for Metastatic Melanoma: Case Series and Clinical Management. (21st January 2018) - Lomax, Anna J.; Lim, Jennifer; Cheng, Robert; Sweeting, Arianne; Lowe, Patricia; McGill, Neil; Shackel, Nicholas; Chua, Elizabeth L.; McNeil, Catriona
Abstract : Immune checkpoint inhibitors (anti-PD-1 and anti-CTLA-4 antibodies) are a standard of care for advanced melanoma. Novel toxicities comprise immune-related adverse events (irAE). With increasing use, irAE require recognition, practical management strategies, and multidisciplinary care. We retrospectively evaluated the incidence, kinetics, and management of irAE in 41 patients receiving anti-PD-1 antibody therapy (pembrolizumab) for advanced melanoma. 63% received prior anti-CTLA-4 antibody therapy (ipilimumab). IrAE occurred in 54%, most commonly dermatological (24%), rheumatological (22%), and thyroid dysfunction (12%). Thyroiditis was characterised by a brief asymptomatic hyperthyroid phase followed by a symptomatic hypothyroid phase requiring thyroxine replacement. Transplant rejection doses of methylprednisolone were necessary to manage refractory hepatotoxicity. A bullous pemphigoid-like skin reaction with refractory pruritus responded to corticosteroids and neuropathic analgesia. Disabling grade 3-4 oligoarthritis required sulfasalazine therapy in combination with steroids. The median interval between the last dose of anti-CTLA-4 antibody and the first dose of anti-PD-1 therapy was 2.0 months (range: 0.4 to 22.4). Toxicities may occur late; this requires vigilance and multidisciplinary management which may allow effective anticancer therapy to continue. Management algorithms for thyroiditis, hypophysitis, arthralgia/arthritis, colitis, steroid-refractory hepatitis, and skin toxicity are discussed.